2023
DOI: 10.1021/acsnano.3c02803
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Mediated Spermidine-Metal-Immunopeptide Nanocomplex for Boosting Ferroptotic Immunotherapy of Lymphoma

Abstract: Immunotherapy as an alternative treatment strategy for B-cell lymphoma is undesirable because of tumor heterogeneity and immune surveillance. Spermidine (SPM), as a regulator of the tumor microenvironment (TME), can facilitate the release of damage-associated molecular patterns (DAMPs) from cancer cells, promote immune recognition, and thus alleviate immune surveillance in the TME. Hence, in this work, self-assembled spermidine-based metal-immunopeptide nanocomplexes (APP-Fe NCs; APP is anti-programmed death l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Theoretically, local hyperthermia may induce cell death and promote the release of damage-associated molecular patterns (DAMPs), an inflammatory response in defending infection [ 38 ]. Hence, it is reasonable to deduce there exists an interplay between hyperthermia and a proinflammatory cell death pathway, i.e., pyroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, local hyperthermia may induce cell death and promote the release of damage-associated molecular patterns (DAMPs), an inflammatory response in defending infection [ 38 ]. Hence, it is reasonable to deduce there exists an interplay between hyperthermia and a proinflammatory cell death pathway, i.e., pyroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies, particularly those focused on nanoparticle‐based approaches, have provided ample evidence for the immunomodulatory effects of inducing ferroptosis in cancer cells. For example, many studies have demonstrated that ferroptotic cancer cells promote immune cell infiltration or activation, thereby improving the immunosuppressive TME [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 62 , 79 , 84 , 85 , 118 , 119 , 120 , 121 , 122 ]. Several studies have also shown that inducing ferroptosis in cancer cells significantly enhances the efficacy of immunotherapy [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: The Crosstalk Between Ferroptosis and Anti‐tumor Immunity In...mentioning
confidence: 99%
“…More preclinical data are needed to promote the progress of clinical applications. In addition, some nanoparticles also respond to external stimuli such as ultrasonic stimulation, heat, pH, and light, and these types of nanoparticles could release drugs in a controlled manner, thereby improving the precision and targeting of drug delivery ( Liu et al, 2023 ; Nie et al, 2023 ), such as pH-sensitive targeting of gastrointestinal and vaginal delivery systems ( Abdella et al, 2023 ), extracellular matrix sensitive GNPs-Dox-Lac ( Liu et al, 2018 ) and magnetic Fe 3 O 4 nanoparticles ( Chen and Hou, 2022 ) At present, physical and chemical targeted nanodrug delivery systems have shown great potential in animal models, but the physical and chemical properties in vivo are dynamic, and how to accurately set the stimulus perception of nanodrug delivery vectors remains to be further studied.…”
Section: Current Strategies For Improving the Properties Of Nanotechn...mentioning
confidence: 99%